Pengaruh Persepsi Kemudahan dan Kegunaan Terhadap Kepuasan Dalam Membangun Loyalitas Pengguna Ovo - oryz agnu dian wulandari; Fauzan Aufa Pradiva; Galang Abdul Aziz (Universitas Islam Bandung, 2020)
ABSTRACT The background of this research is the development of technology can facilitate all transactaion, especially in making payment digitally or often referred to as digital payment. OVO is a digital payment application that has various benerfit and convenience for people in their daily liver to make payment transaction. Detemination of the sample in this study is the purposive sampling method with certain criteria, nemely the Purwokerto city community who have used OVO at least 3 times in making payment transaction. The result of this study are perceived ease of use and perceive usefullness have a positive and significant effect on satisfaction, it is shown by each independent variable shows the result of the calculation of the number of estimates has a positive value and the probability value og each variable has a of P < 0,05. In addition, customer satisfaction variables also have a positive anda significant effect on loyalty. With these results it shows that the OVO apllication has been widely accepted by the public at large, in addition to the OVO application can facilitate its ussers and provide great benefit in making payment transaction digitally.Keywords: satisfaction, loyality, perceived ease of use, perceived usefulness, OVO